Limit Cycles Bifurcating from an Invisible Fold–Fold in Planar Piecewise Hamiltonian Systems - de Carvalho Braga, Denis; Fernandes da Fonseca, Alexander; Gonçalves, Luiz Fernando [UNESP]; Mello, Luis Fernando (Springer Nature, 2020)
The aim of this article is twofold. Firstly, we study the existence of limit cycles in a family of piecewise smooth vector fields corresponding to an unfolding of an invisible fold–fold singularity. More precisely, given a positive integer k, we prove that this family has exactly k hyperbolic crossing limit cycles in a suitable neighborhood of this singularity. Secondly, we provide a complete study relating the existence and stability of these crossing limit cycles with the limit cycles of the family of smooth vector fields obtained by the regularization method. This relationship is obtained by studying the equivalence between the signs of the Lyapunov coefficients of the family of piecewise smooth vector fields and the ones of its regularization.
Keywords: Bifurcation; Fold–fold singularity; Hamiltonian vector field; Limit cycle; Piecewise smooth vector field; Regularization